Attacus atlas (L.) sericin extract as an effective UV Protectant of Bacillus thuringiensis serotype kurstaki for controlling Spodoptera litura (Fab.) - Nindita Sabila Ningtyas; Rahmatullah Rahmatullah; Aryo Seto Pandu Wiranto; Nadya Sofia Siti Sa’adah; Hipny Alwandri; Asma’ Asma’; Tiara Purti Salsabila; Hanindyo Adi; Sukirno Sukirno (Journal of Tropical Biodiversity and Biotechnology, 2023)
Bacillus thuringiensis serotype kurstaki is an entomopathogenic bacteria commonly used to control the cutworm Spodoptera litura (Fab.). However, B. thuringiensis has disadvantage of being easily degraded due to exposed sunlight. The objective of this research was to determine the effectiveness of adding A. atlas (L.) cocoon extract as UV protectant B. thuringiensis to the mortality of S. litura. This research formulated 2.5% of the original substance of A. atlas cocoon extract and B. thuringiensis serotype kurstaki strain HD-7 applied from commercial product DiPel-WP®. The formulation was exposed to sunlight for 0, 1, 2, and 3 weeks. The suspension treated for 20 individuals of first instar larvae S. litura shifted into the artificial diet using 3-5 replicates. The scanning electron microscope (SEM) method began from a sample that was vacuumed, sample coated, and observed on SEM with the electron in a certain level probe. This research showed that the mortality of S. litura decreased with the growth of S. litura. The mortality of S. litura achieved 20%-100% mortality after treatments. The A. atlas cocoon extract was effective as UV protectant B. thuringiensis for three weeks of exposure to sunlight. The SEM analysis represented that formulation of B. thuringiensis and A. atlas cocoon extract sunlight exposure for one week has harsher surface than exposed during three weeks.